Expanding the phenotype of TARDBP mutation in a Tunisian family with clinical phenotype heterogeneity. Issue 7 (2nd October 2022) - Kacem, Imen; Sghaier, Ikram; Ticozzi, Nicola; Mrabet, Saloua; Paverelli, Silvia; Nasri, Amina; Ratti, Antonia; Ben Djebara, Mouna; Gargouri-Berrachid, Amina; Silani, Vincenzo; Gouider, Riadh
Abstract: We describe a Tunisian family carrier of the same rare mutation in TARDBP but developing different neurodegenerative disease with heterogenous features. We explored the possible genetic modifiers leading to the observed intrafamilial phenotypic variability. Genetic analysis identified TARDBP p.G294A mutation among4 members. Additionally, the ALS case was muted in GBA . While the three cases of AD were carriers of PRKN and GBA mutations. Finally, the FTD-parkinsonism patient was mutated for LRRK2 p.G2019S that might increase his susceptibility to develop Parkinsonism spectrum. Genetic variants of TARDBP may influence the clinical manifestation in ALS case.